Modification of grassy weeds as potential used cooking oil absorbent - Mohammad Safwan Ariffin (2012)
Oil pollution is recognized as one of the most, frequent type of water pollution. Oil spills and careless disposal of oil wastes into drainage systems can ultimately reach surface water levels, ground water and land areas. Some can make blockage to pipe sewer and send sewage backward. This sewage could harm the environment. Recent study show that most of fiber like kenaf, rice stalk and grass residue have the ability to absorb the oil. Grassy weed as fiber have potential ability to absorb the oil. Study also shown this fiber if treated with sodium hydroxide, it will increase the ability of fiber to absorb more oil. This study is conducted to analyze the potential of grass weed to absorb the oil and to know how much the oil can absorbed. From this study, it shown that the highest sorption capacity that can be achieved is in 2 grams of grass weed and 30 minutes exposure to the oil that is achieving to 224% of sorption capacity. After the grass weed treated with sodium hydroxide, the result showed that sorption capacity increase about 61% from highest sorption capacity of untreated grass. Therefore, this study proves that grass weed can absorb oil and increase it potential when treated with sodium hydroxide.